Antibacterial stain-resistant flax composite fabric and preparation method thereof
By modifying and blending flax fibers and combining quaternary acrylamide-tetrafluoroethylene copolymer grafting, the dirt adhesion and bacterial growth problems caused by the hydrophilicity of flax fabrics are solved, and the antibacterial and stain resistance of the fabric is improved.
Patent Information
- Application Number
- CN202411889685.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Because of its strong hydrophilicity, linen fabrics are prone to dirt and are prone to breed bacteria after absorbing moisture, resulting in frequent cleaning and odor.
Modified flax fiber, modal fiber and polyester fiber are blended and grafted to the surface of flax fiber by quaternary acrylamide-tetrafluoroethylene copolymer, reducing the grime adhesion ability and improving antibacterial properties.
It improves the antibacterial and stain resistance of the fabric, reduces dirt adhesion and odor generation, and extends the service life of the fabric.
Smart Images

Figure BDA0005200327270000071 
Figure BDA0005200327270000081 
Figure BDA0005200327270000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric preparation, and in particular to an antibacterial and stain-resistant flax composite fabric and a preparation method thereof. Background Art
[0002] Flax is the earliest natural plant fiber used by humans, with a history of more than 10,000 years. As flax has excellent moisture absorption and moisture conductivity, and can absorb more than 20 times its own weight in water, linen fabrics are breathable, cool, crisp and comfortable, and are very popular among consumers, with a very broad market.
[0003] Although linen fabric has many advantages, due to its strong hydrophilicity, dirt is easily attached to the surface of linen fabric, which requires frequent cleaning. In addition, since linen fabric absorbs moisture well, it is easy to breed bacteria after absorbing sweat, causing odor when the fabric is worn. Summary of the invention
[0004] In order to solve the above problems, the present invention provides an antibacterial and stain-resistant linen composite fabric and a preparation method thereof.
[0005] The technical scheme of the present invention is: an antibacterial and stain-resistant flax composite fabric, which is made by blending the following raw materials in parts by weight: 40-60 parts of modified flax fiber, 20-30 parts of modal fiber, and 15-20 parts of polyester fiber.
[0006] Description: The above composite fabric is blended by modified flax fiber, modal fiber and polyester fiber, so that the woven composite fabric has good strength, and the surface tension of the flax fiber is reduced by modification, so that dirt is not easy to adhere to the flax fiber, and the modified flax fiber has good antibacterial properties, which can reduce the odor generated during the use of the composite fabric.
[0007] Furthermore, the preparation method of the modified flax fiber comprises the following steps:
[0008] S1. Dissolve acrylamide in deionized water and stir for 5 to 10 minutes to obtain an acrylamide solution; the mass ratio of acrylamide to deionized water is 1:3 to 5;
[0009] S2. Using a sodium hydroxide solution with a mass concentration of 10-15%, the pH value of the acrylamide solution is adjusted to 8-10, the acrylamide solution is heated to 60-70° C., and then ethyl bromide is added to the acrylamide solution under stirring. After keeping the temperature for 4-8 hours, the pH value of the acrylamide solution is adjusted to neutral using dilute hydrochloric acid with a mass concentration of 8-10%, to obtain a quaternized acrylamide solution; the amount of ethyl bromide added accounts for 4-6% of the total mass of the acrylamide solution;
[0010] S3, placing the quaternized acrylamide solution into a reaction kettle, soaking the flax fiber in the quaternized acrylamide solution, and then keeping the reaction kettle at 60-80° C. for 10-12 hours; wherein the mass ratio of the flax fiber to the quaternized acrylamide solution is 1:5-6;
[0011] During the heat preservation process, tetrafluoroethylene is introduced into the reactor. Whenever the pressure in the reactor reaches 2-3 MPa, the introduction of tetrafluoroethylene is stopped, and an initiator is added into the reactor. When the pressure in the reactor drops to 0.4-0.6 MPa, the introduction of tetrafluoroethylene is resumed until the heat preservation is completed. The single addition amount of the initiator is 1-2% of the initial mass of the acrylamide solution.
[0012] S4. After the heat preservation is completed, the flax fiber is taken out, and the modified flax fiber is obtained after washing and drying.
[0013] Description: The above modification step reduces the adhesion of dirt on the surface of flax fiber by quaternizing acrylamide and then grafting the quaternized acrylamide-tetrafluoroethylene copolymer to the surface of flax fiber. The quaternized acrylamide-tetrafluoroethylene copolymer can effectively improve the antibacterial properties of flax fiber and reduce bacterial growth.
[0014] Furthermore, in step S3, the flax fibers are soaked in a sodium hydroxide solution with a mass concentration of 8 to 12% for 20 to 30 minutes before being soaked in the acrylamide solution.
[0015] Description: Soaking in sodium hydroxide solution can remove the pectin layer, hemicellulose xylan and lignin on the surface of flax fiber, making the fiber surface smooth and clean, which is convenient for subsequent processing.
[0016] Furthermore, in step S3, the introduction rate of tetrafluoroethylene is 2 to 4 L / min.
[0017] Note: Limiting the introduction rate of tetrafluoroethylene can ensure the reaction rate and ensure that the reaction proceeds fully.
[0018] Furthermore, in step S4, the washing is performed by rinsing with a sodium carbonate solution having a mass concentration of 2 to 4%.
[0019] Description: Using sodium carbonate for washing can effectively remove residues on the surface of flax fibers, and the cost of sodium carbonate is low and it is safe to use.
[0020] Furthermore, in step S4, the drying temperature is 70-80° C., and the drying time is 12-14 hours.
[0021] Note: Defining the drying parameters can ensure that the surface moisture of the modified flax fiber is fully removed, so as to avoid the residual moisture on the surface of the modified flax fiber affecting the subsequent blending steps.
[0022] On the other hand, the present invention provides a method for preparing the above-mentioned antibacterial and stain-resistant linen composite fabric, comprising the following steps:
[0023] 1) adding modified flax fiber, modal fiber and polyester fiber according to the weight parts into a blending machine for blending, and then weaving through a textile machine to obtain a fabric;
[0024] 2) The fabric is immersed in the finishing liquid for 2 to 4 times, the bath ratio during immersion is 1:20-25, the temperature of the finishing liquid is 60-70°C, the single immersion time is 10-15 minutes, and the fabric is pressed by a rolling mill after each immersion, and the rolling rate of a single pressing is 30-50%.
[0025] 3) After the impregnation is completed, the fabric is dried to obtain a composite fabric.
[0026] Description: The above preparation method obtains the fabric by blending and weaving, and the fabric is impregnated and pressed multiple times to enable the fabric to fully absorb the finishing liquid, further improving the antibacterial and stain resistance of the fabric.
[0027] Furthermore, the finishing liquid comprises the following components by weight: 6-12 parts of silver nitrate, 3-6 parts of sodium hypophosphite, 5-10 parts of polyvinyl pyrrolidone, 2-4 parts of boric acid, and 60-70 parts of deionized water.
[0028] Description: The above finishing liquid has excellent antibacterial performance. After the fabric absorbs the finishing liquid, the antibacterial performance can be effectively improved. The finishing liquid can also improve the surface properties of the fabric, making it difficult for the fabric to be soaked by water and oil, thereby improving the anti-fouling performance.
[0029] Furthermore, after each rolling process, a plasma treatment machine is used to perform plasma treatment on the fabric. The initial power of the plasma treatment machine is 10-15 kW, the frequency is 15-20 kHz, and the power of the plasma treatment machine is reduced by 1-2 kW each time compared with the previous plasma treatment.
[0030] Note: Since the finishing liquid is not easy to soak the flax fiber after modification, plasma treatment can make the effective ingredients in the finishing liquid enter the fiber, ensuring the finishing effect of the finishing liquid, and gradually reducing the power of the plasma treatment machine to ensure the integrity of the fiber structure.
[0031] The beneficial effects of the present invention are:
[0032] (1) The composite fabric of the present invention is blended by modified flax fiber, modal fiber and polyester fiber, so that the woven composite fabric has good strength, and the surface tension of the flax fiber is reduced by modification, so that dirt is not easy to adhere to the flax fiber, and the modified flax fiber has good antibacterial properties, which can reduce the odor generated during the use of the composite fabric.
[0033] (2) In the modification step of the present invention, acrylamide is quaternized and then the quaternized acrylamide-tetrafluoroethylene copolymer is grafted onto the surface of the flax fiber, thereby reducing the adhesion of dirt on the surface of the flax fiber. The quaternized acrylamide-tetrafluoroethylene copolymer can effectively improve the antibacterial properties of the flax fiber and reduce bacterial growth.
[0034] (3) The preparation method of the present invention obtains the fabric by blending and weaving, and the fabric is impregnated and pressed multiple times to enable the fabric to fully absorb the finishing liquid, thereby further improving the antibacterial and stain-resistant properties of the fabric. DETAILED DESCRIPTION
[0035] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0036] Example 1: An antibacterial and stain-resistant linen composite fabric, the composite fabric is made by blending the following raw materials in parts by weight: 50 parts of modified linen fiber, 25 parts of modal fiber, and 18 parts of polyester fiber;
[0037] The preparation method of modified flax fiber comprises the following steps:
[0038] S1. Dissolve acrylamide in deionized water and stir for 8 minutes to obtain an acrylamide solution; wherein the mass ratio of acrylamide to deionized water is 1:4;
[0039] S2. Using a sodium hydroxide solution with a mass concentration of 12%, the pH value of the acrylamide solution is adjusted to 9, the acrylamide solution is heated to 65° C., and then ethyl bromide is added to the acrylamide solution under stirring. After keeping the temperature for 6 hours, the pH value of the acrylamide solution is adjusted to neutral using dilute hydrochloric acid with a mass concentration of 9%, to obtain a quaternized acrylamide solution; wherein the amount of ethyl bromide added accounts for 5% of the total mass of the acrylamide solution;
[0040] S3, putting the quaternized acrylamide solution into a reactor, soaking the flax fiber in the quaternized acrylamide solution, and then keeping the reactor at 70°C for 11 hours; wherein the mass ratio of the flax fiber to the quaternized acrylamide solution is 1:5.5; before soaking the flax fiber in the acrylamide solution, soak it in a sodium hydroxide solution with a mass concentration of 10% for 25 minutes;
[0041] During the heat preservation process, tetrafluoroethylene is introduced into the reactor. Whenever the pressure in the reactor reaches 2.5 MPa, the introduction of tetrafluoroethylene is stopped, and an initiator is added into the reactor. When the pressure in the reactor drops to 0.5 MPa, the introduction of tetrafluoroethylene is resumed until the heat preservation is completed. The single addition amount of the initiator is 1.5% of the initial mass of the acrylamide solution. The introduction rate of tetrafluoroethylene is 3 L / min.
[0042] S4, after the heat preservation is completed, the flax fiber is taken out, and the modified flax fiber is obtained after washing and drying; wherein, the washing is carried out by rinsing with a sodium carbonate solution with a mass concentration of 3%; the drying temperature is 75° C., and the drying time is 13 hours;
[0043] The method for preparing the above-mentioned flax composite fabric comprises the following steps:
[0044] 1) adding modified flax fiber, modal fiber and polyester fiber to a blending machine according to weight for blending, and then weaving on a textile machine to obtain a fabric; the blending and weaving used in this embodiment are both existing technologies and will not be described in detail here;
[0045] 2) The fabric is immersed in the finishing liquid for 3 times, the bath ratio during immersion is 1:22, the temperature of the finishing liquid is 65°C, the single immersion time is 12 minutes, and the fabric is rolled using a rolling mill after each immersion, and the rolling rate of a single rolling is 40%; after each rolling, the fabric is plasma treated with a plasma treatment machine, the initial power of the plasma treatment machine is 12kW, the frequency is 18kHz, and the power of the plasma treatment machine is reduced by 1.5kW each time compared with the previous plasma treatment;
[0046] The finishing solution includes the following components by weight: 9 parts of silver nitrate, 5 parts of sodium hypophosphite, 8 parts of polyvinyl pyrrolidone, 3 parts of boric acid, and 65 parts of deionized water;
[0047] 3) After the impregnation is completed, the fabric is dried to obtain a composite fabric.
[0048] Example 2: This example is basically the same as Example 1, except that the composite fabric is made by blending the following raw materials in parts by weight: 40 parts of modified flax fiber, 20 parts of modal fiber, and 15 parts of polyester fiber.
[0049] Example 3: This example is basically the same as Example 1, except that the composite fabric is made by blending the following raw materials in parts by weight: 60 parts of modified flax fiber, 30 parts of modal fiber, and 20 parts of polyester fiber.
[0050] Example 4: This example is basically the same as Example 1, except that the pH value of the acrylamide solution is adjusted to 8 using a sodium hydroxide solution with a mass concentration of 12%.
[0051] Example 5: This example is basically the same as Example 1, except that the pH value of the acrylamide solution is adjusted to 10 using a sodium hydroxide solution with a mass concentration of 12%.
[0052] Example 6: This example is basically the same as Example 1, except that the amount of ethyl bromide added is 4% of the total mass of the acrylamide solution.
[0053] Example 7: This example is basically the same as Example 1, except that the amount of ethyl bromide added is 6% of the total mass of the acrylamide solution.
[0054] Example 8: This example is basically the same as Example 1, except that the mass ratio of flax fiber to quaternized acrylamide solution is 1:5.
[0055] Example 9: This example is basically the same as Example 1, except that the mass ratio of flax fiber to quaternized acrylamide solution is 1:6.
[0056] Example 10: This example is basically the same as Example 1, except that tetrafluoroethylene is introduced into the reactor during the insulation process, and whenever the pressure in the reactor reaches 2MPa, the introduction of tetrafluoroethylene is stopped and an initiator is added to the reactor.
[0057] Example 11: This example is basically the same as Example 1, except that tetrafluoroethylene is introduced into the reactor during the insulation process, and whenever the pressure in the reactor reaches 3MPa, the introduction of tetrafluoroethylene is stopped and an initiator is added to the reactor.
[0058] Example 12: This example is basically the same as Example 1, except that the introduction rate of tetrafluoroethylene is 2 L / min.
[0059] Example 13: This example is basically the same as Example 1, except that the introduction rate of tetrafluoroethylene is 4 L / min.
[0060] Example 14: This example is basically the same as Example 1, except that the single addition amount of the initiator is 1% of the initial mass of the acrylamide solution.
[0061] Example 15: This example is basically the same as Example 1, except that the single addition amount of the initiator is 2% of the initial mass of the acrylamide solution.
[0062] Example 16: This example is basically the same as Example 1, except that the fabric is immersed in the finishing liquid for 2 to 4 times.
[0063] Example 17: This example is basically the same as Example 1, except that the fabric is immersed in the finishing liquid for 2 to 4 times.
[0064] Embodiment 18: This embodiment is basically the same as Embodiment 1, except that the initial power of the plasma processor is 10 kW and the frequency is 15 kHz.
[0065] Example 19: This example is basically the same as Example 1, except that the initial power of the plasma processor is 15 kW and the frequency is 20 kHz.
[0066] Embodiment 20: This embodiment is basically the same as Embodiment 1, except that the power of the plasma processor is reduced by 1 kW each time the plasma treatment is performed compared with the previous time.
[0067] Embodiment 21: This embodiment is basically the same as Embodiment 1, except that the power of the plasma processor is reduced by 2 kW each time the plasma treatment is performed compared with the previous time.
[0068] Example 22: This example is basically the same as Example 1, except that the finishing solution comprises the following components by weight: 6 parts of silver nitrate, 3 parts of sodium hypophosphite, 5 parts of polyvinyl pyrrolidone, 2 parts of boric acid, and 60 parts of deionized water.
[0069] Example 23: This example is basically the same as Example 1, except that the finishing solution comprises the following components by weight: 12 parts of silver nitrate, 6 parts of sodium hypophosphite, 10 parts of polyvinyl pyrrolidone, 4 parts of boric acid, and 70 parts of deionized water.
[0070] Comparative Example 1: Taking Example 1 as a reference, the modified flax fiber was replaced with ordinary flax fiber.
[0071] Comparative Example 2: Using Example 1 as a reference, the quaternized acrylamide solution was replaced with an acrylamide solution.
[0072] Comparative Example 3: Taking Example 1 as a reference, tetrafluoroethylene was continuously introduced during the reaction, and the initiator was added once.
[0073] Comparative Example 4: Using Example 1 as a reference, no plasma treatment was performed after rolling.
[0074] Comparative Example 5: Taking Example 1 as a reference, the power of the plasma processor is maintained at 12 kW without change.
[0075] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the composite fabric, the tensile elastic recovery rate of the composite fabric of each embodiment was tested by the method described in FZ-T70006-2022, the antibacterial rate of the composite fabric of each embodiment against Escherichia coli was tested by the bacterial liquid absorption method, and the oil repellency of the composite fabric of each embodiment according to the AATCC118-1997 standard was tested. The specific exploration is as follows:
[0076] Experimental Example 1: Investigating the influence of composite fabric composition on composite fabric performance
[0077] Using Examples 1 to 3 and Comparative Example 1 as experimental comparison, the performance of composite fabrics with different components is shown in Table 1 below:
[0078] Table 1 Composite fabric properties under different composite fabric components
[0079] Group Escherichia coli inhibition rate Tensile elastic recovery Oil repellency grade Example 1 91.2% 46.3% 4 Example 2 89.6% 51.8% 4 Example 3 90.5% 38.6% 4 Comparative Example 1 80.8% 43.5% 3
[0080] It can be seen from the data in Table 1 that, compared with Examples 1, 2, and 3, the higher the proportion of modified flax fiber, the higher the Escherichia coli antibacterial rate of the composite fabric, but the tensile elastic recovery rate will decrease. The components of the composite fabric are selected as needed during the production process, and the oil repellency level of the composite fabrics of Examples 1 to 3 all reaches level four, indicating that the composite fabric of the present invention has good stain resistance.
[0081] Compared with Comparative Example 1, Example 1 shows that after the modified flax fiber is replaced by ordinary flax fiber, the antibacterial rate of the composite fabric is significantly reduced and the oil repellency level is reduced, which indicates that the modified flax fiber can significantly improve the antibacterial and stain resistance of the composite fabric. Therefore, the composite fabric composition selected in Example 1 is optimal.
[0082] Experimental Example 2: Investigating the influence of preparation parameters of quaternized acrylamide solution on the performance of composite fabrics
[0083] Using Example 1, Examples 4 to 9 and Comparative Example 2 as experimental comparisons, the composite fabric properties obtained under different preparation parameters of the quaternized acrylamide solution are shown in Table 2 below:
[0084] Table 2 Composite fabrics with different preparation parameters of quaternized acrylamide solution
[0085] Group Escherichia coli inhibition rate Tensile elastic recovery Oil repellency grade Example 1 91.2% 46.3% 4 Example 4 89.5% 44.2% 4 Example 5 89.9% 45.3% 4 Example 6 87.9% 44.8% 4 Example 7 88.3% 45.1% 4 Example 8 90.6% 45.6% 4 Example 9 90.2% 45.1% 4 Comparative Example 2 82.3% 44.3% 4
[0086] From the data in Table 2, it can be seen that, by comparing Example 1 and Examples 4 to 9, the pH value of the acrylamide solution is too high or too low, the amount of ethyl bromide added is too high or too low, and the proportion of the quaternized acrylamide solution is too high or too low, which will lead to a decrease in the antibacterial rate of Escherichia coli of the composite fabric. Among them, the antibacterial rate of Escherichia coli in Example 1 is the highest. This may be because under the preparation parameters of the quaternized acrylamide solution in Example 1, the conversion rate of quaternized acrylamide is the highest. Therefore, the preparation parameters of the quaternized acrylamide solution selected in Example 1 are optimal.
[0087] Compared with Comparative Example 2, Example 1 shows that after the quaternized acrylamide solution is replaced by acrylamide solution, the antibacterial rate of Escherichia coli of the composite fabric is significantly reduced. This may be because the antibacterial effect of acrylamide that has not undergone quaternization reaction is poor. Therefore, the preparation method of modified flax fiber selected in Example 1 is the best.
[0088] Experimental Example 3: Investigating the influence of modified flax fiber preparation parameters on the performance of composite fabrics
[0089] Using Example 1, Examples 10 to 15 and Comparative Example 3 as experimental comparisons, the properties of the composite fabrics obtained under different preparation parameters of the modified flax fiber are shown in Table 3 below:
[0090] Table 3 Composite fabrics of modified flax fiber under different preparation parameters
[0091]
[0092]
[0093] It can be seen from the data in Table 3 that, compared with Examples 10 to 15, Example 1 has the following conditions: the pressure in the reactor is too high or too low, the rate of tetrafluoroethylene introduction is too high or too low, and the single addition amount of the initiator is too high or too low, which will lead to a decrease in the antibacterial rate of Escherichia coli of the composite fabric. This may be because under the modified flax fiber preparation parameters of Example 1, the conversion rate of the quaternized acrylamide-tetrafluoroethylene copolymer is the highest and can be fully grafted onto the flax fiber. Therefore, the modified flax fiber preparation parameters selected in Example 1 are optimal.
[0094] Compared with Comparative Example 3, Example 1 shows that after continuous introduction of tetrafluoroethylene during the reaction and the one-time addition of the initiator, the Escherichia coli antibacterial rate of the composite fabric is significantly reduced. This may be because the one-time addition of the initiator causes the reaction in the reactor to be too violent, resulting in damage to the structure of the flax fiber. Therefore, the preparation method of the modified flax fiber selected in Example 1 is the best.
[0095] Experimental Example 4: Investigating the influence of finishing parameters on the performance of composite fabrics
[0096] Using Example 1, Examples 16 to 23 and Comparative Examples 4 to 5 as experimental comparisons, the performance of the composite fabric under different finishing parameters is shown in Table 4 below:
[0097] Table 4 Composite fabrics under different finishing parameters
[0098]
[0099]
[0100] It can be seen from the data in Table 4 that, compared with Examples 1, 16, and 17: as the number of immersions increases, the antibacterial performance of the composite fabric gradually improves until the antibacterial performance of the composite fabric of Example 1 reaches the highest. As the number of immersions continues to increase, the antibacterial performance of the composite fabric begins to have no obvious change. Therefore, from the perspective of time cost, the number of immersions selected in Example 1 is the best;
[0101] Compared with Examples 18 to 21, Example 1 shows that the initial power of the plasma treatment machine is too high or too low, and the power variation is too high or too low, which will lead to a decrease in the antibacterial performance of the composite fabric. This may be because the finishing effect of the finishing liquid is best under the initial power and power variation of the plasma treatment machine selected in Example 1. Therefore, the initial power and power variation of the plasma treatment machine selected in Example 1 are optimal.
[0102] Compared with Examples 22 and 23, Example 1 has the highest Escherichia coli antibacterial rate of the composite fabric of Example 1. This may be because under the finishing liquid composition of Example 1, the fabric has the best absorption effect on the finishing liquid, so the finishing liquid composition selected in Example 1 is optimal.
[0103] Compared with Comparative Examples 4 and 5, the embodiment of the present invention does not perform plasma treatment after rolling or keeps the power of the plasma treatment machine unchanged, which will lead to a decrease in the antibacterial rate of Escherichia coli of the composite fabric. This may be because plasma treatment can improve the absorption effect of the fabric on the finishing liquid. Therefore, the plasma treatment method selected in Example 1 is the best.
Claims
1. An antibacterial and stain-resistant linen composite fabric, characterized in that: The composite fabric is made by blending the following raw materials in parts by weight: 40-60 parts of modified flax fiber, 20-30 parts of modal fiber, and 15-20 parts of polyester fiber.
2. The antibacterial and stain-resistant linen composite fabric according to claim 1, characterized in that: The preparation method of the modified flax fiber comprises the following steps: S1. Dissolve acrylamide in deionized water and stir for 5 to 10 minutes to obtain an acrylamide solution; the mass ratio of acrylamide to deionized water is 1:3 to 5; S2. Using a sodium hydroxide solution with a mass concentration of 10-15%, the pH value of the acrylamide solution is adjusted to 8-10, the acrylamide solution is heated to 60-70° C., and then ethyl bromide is added to the acrylamide solution under stirring. After keeping the temperature for 4-8 hours, the pH value of the acrylamide solution is adjusted to neutral using dilute hydrochloric acid with a mass concentration of 8-10%, to obtain a quaternized acrylamide solution; the amount of ethyl bromide added accounts for 4-6% of the total mass of the acrylamide solution; S3, placing the quaternized acrylamide solution into a reaction kettle, soaking the flax fiber in the quaternized acrylamide solution, and then keeping the reaction kettle at 60-80° C. for 10-12 hours; wherein the mass ratio of the flax fiber to the quaternized acrylamide solution is 1:5-6; During the heat preservation process, tetrafluoroethylene is introduced into the reactor. Whenever the pressure in the reactor reaches 2-3 MPa, the introduction of tetrafluoroethylene is stopped, and an initiator is added into the reactor. When the pressure in the reactor drops to 0.4-0.6 MPa, the introduction of tetrafluoroethylene is resumed until the heat preservation is completed. The single addition amount of the initiator is 1-2% of the initial mass of the acrylamide solution. S4. After the heat preservation is completed, the flax fiber is taken out, and the modified flax fiber is obtained after washing and drying.
3. The antibacterial and stain-resistant linen composite fabric according to claim 2, characterized in that: In step S3, the flax fibers are soaked in a sodium hydroxide solution with a mass concentration of 8 to 12% for 20 to 30 minutes before being soaked in the acrylamide solution.
4. The antibacterial and stain-resistant linen composite fabric according to claim 2, characterized in that: In step S3, the introduction rate of tetrafluoroethylene is 2 to 4 L / min.
5. The antibacterial and stain-resistant linen composite fabric according to claim 2, characterized in that: In step S4, the washing is performed by rinsing with a sodium carbonate solution having a mass concentration of 2 to 4%.
6. The antibacterial and stain-resistant linen composite fabric according to claim 2, characterized in that: In step S4, the drying temperature is 70-80° C., and the drying time is 12-14 hours.
7. A method for preparing an antibacterial and stain-resistant linen composite fabric, used for preparing an antibacterial and stain-resistant linen composite fabric as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: 1) adding modified flax fiber, modal fiber and polyester fiber according to the weight parts into a blending machine for blending, and then weaving through a textile machine to obtain a fabric; 2) The fabric is immersed in the finishing liquid for 2 to 4 times, the bath ratio during immersion is 1:20-25, the temperature of the finishing liquid is 60-70°C, the single immersion time is 10-15 minutes, and the fabric is pressed by a rolling mill after each immersion, and the rolling rate of a single pressing is 30-50%. 3) After the impregnation is completed, the fabric is dried to obtain a composite fabric.
8. The method for preparing an antibacterial and stain-resistant linen composite fabric according to claim 7, characterized in that: The finishing liquid comprises the following components by weight: 6-12 parts of silver nitrate, 3-6 parts of sodium hypophosphite, 5-10 parts of polyvinyl pyrrolidone, 2-4 parts of boric acid, and 60-70 parts of deionized water.
9. The method for preparing an antibacterial and stain-resistant linen composite fabric according to claim 7, characterized in that: After each rolling process, a plasma treatment machine is used to treat the fabric with plasma. The initial power of the plasma treatment machine is 10-15 kW, the frequency is 15-20 kHz, and the power of the plasma treatment machine is reduced by 1-2 kW each time compared with the previous plasma treatment.
Citation Information
Patent Citations
Method for preparing antibacterial coating material
CN103409004A
Antibiosis fabric
CN106567176A
Anti-pollution antibacterial PTFE oil-water separation membrane and preparation method thereof
CN113069938A
High-temperature-resistant oil-resistant Teflon cable tie and preparation method thereof
CN117004122A
Anti-contaminant treatment for papermaking fabrics
US5207873A